2013
DOI: 10.1144/sp390.15
|View full text |Cite
|
Sign up to set email alerts
|

3D interpretation by integrating seismic and potential field data in the vicinity of the proposed COSC-1 drill site, central Swedish Caledonides

Abstract: The scientific drilling project COSC (Collisional Orogeny in the Scandinavian Caledonides), designed to study key questions concerning orogenic processes, aims to drill two fully cored boreholes to depths of c. 2.5 km each at carefully selected locations in west-central Sweden. The first of these, COSC-1, is scheduled for start late spring 2014 and will target the Seve Nappe Complex, characterized by inverted metamorphism and with parts that have evidently been subjected to hot ductile extrusion. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…The uppermost 500 m was poorly imaged due to the acquisition geometry. Potential field modelling (Hedin et al, 2014) also indicated the base of the Seve Nappe Complex to be at about 2 km depth at the COSC-1 site, consistent with the seismic data.…”
Section: Preliminary Scientific Assessmentsupporting
confidence: 74%
“…The uppermost 500 m was poorly imaged due to the acquisition geometry. Potential field modelling (Hedin et al, 2014) also indicated the base of the Seve Nappe Complex to be at about 2 km depth at the COSC-1 site, consistent with the seismic data.…”
Section: Preliminary Scientific Assessmentsupporting
confidence: 74%
“…In the present summary, we focus on the area from Are toÖstersund in western Jämtland (yellow square in Figs 1 and 2), where we collected MT data. The detailed geology of this area has been previously described by Gee et al (2010), Hedin et al (2012Hedin et al ( , 2014 and Juhlin et al (2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…The location of the first borehole, COSC-1, targeting the Seve Nappe Complex was proposed mainly based on the seismic results. A 3-D interpretation of the Seve Nappe Complex presented by Hedin et al (2014) was based on surface geology, available seismic sections and 3-D inverse modelling of more than 300 ground gravity measurements from SGU. A maximum depth extent of 2.5 km of the Seve Nappe Complex was supported by the inversion models, an interpretation generally consistent with the reflection seismic image.…”
Section: Previous Geophysical Studiesmentioning
confidence: 99%
See 2 more Smart Citations